2009
DOI: 10.1200/jco.2008.21.1128
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Alemtuzumab in Fludarabine-Refractory Chronic Lymphocytic Leukemia: Clinical Results and Prognostic Marker Analyses From the CLL2H Study of the German Chronic Lymphocytic Leukemia Study Group

Abstract: Subcutaneous alemtuzumab appears as effective and safe as intravenous alemtuzumab in fludarabine-refractory CLL. Subcutaneous administration should be the preferred delivery route because of its efficacy, convenience, improved adverse effect profile, and cost savings. In contrast to chemotherapy-based therapy, alemtuzumab treatment overcomes the adverse prognostic impact of VH mutation status, TP53 mutation, and genomic aberrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
151
0
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 246 publications
(167 citation statements)
references
References 37 publications
10
151
0
6
Order By: Relevance
“…The OR for all patients was 62%. This rate was comparable with that achieved in pretreated patients within the REACH trial with the FCR regimen and with FC plus alemtuzumab (OR: 69.9% and 67%, respectively) [27,28], and higher than that reported for alemtuzumab monotherapy (OR: 34%) [5]. It is noteworthy that the REACH trial did not include fludarabinerefractory patients, and the 17p deletion was present in only 7% of the patients.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The OR for all patients was 62%. This rate was comparable with that achieved in pretreated patients within the REACH trial with the FCR regimen and with FC plus alemtuzumab (OR: 69.9% and 67%, respectively) [27,28], and higher than that reported for alemtuzumab monotherapy (OR: 34%) [5]. It is noteworthy that the REACH trial did not include fludarabinerefractory patients, and the 17p deletion was present in only 7% of the patients.…”
Section: Discussionsupporting
confidence: 72%
“…17p and 11q deletions are found in around 5% and 20% of cases at diagnosis (de novo deletions), respectively, but can also be acquired during the evolution of the disease. Indeed, the incidence of 17p-in patients with relapsed or refractory CLL can be up to 30% [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficiency was the same in all genetic subgroups, notably in 17p-and 11q-deletion, TP53 mutation and unmutated IGHV status (Fig. 4) [14].…”
Section: Alemtuzumabmentioning
confidence: 80%
“…The phase II GCLLSG CLL2H trial evaluated the safety and efficacy of subcutaneous alemtuzumab in patients with fludarabine-refractory CLL, and reported that OR was 34% (4% CR and 30% PR), median PFS was 7.7 months, and median OS was 19.1 months [56]. Efficacy did not vary significantly between genetic subgroups, indicating that alemtuzumab treatment could overcome the adverse prognostic impact of IGHV mutation status, TP53 mutation, and genomic aberrations.…”
Section: Clanahan Et Al Treatment Of Chronic Lymphocytic Leukemiamentioning
confidence: 99%